2021 roadmap on lithium sulfur batteries. (25th March 2021) - Robinson, James B; Xi, Kai; Kumar, R Vasant; Ferrari, Andrea C; Au, Heather; Titirici, Maria-Magdalena; Parra-Puerto, Andres; Kucernak, Anthony; Fitch, Samuel D S; Garcia-Araez, Nuria; Brown, Zachary L; Pasta, Mauro; et al.
Abstract: Batteries that extend performance beyond the intrinsic limits of Li-ion batteries are among the most important developments required to continue the revolution promised by electrochemical devices. Of these next-generation batteries, lithium sulfur (Li–S) chemistry is among the most commercially mature, with cells offering a substantial increase in gravimetric energy density, reduced costs and improved safety prospects. However, there remain outstanding issues to advance the commercial prospects of the technology and benefit from the economies of scale felt by Li-ion cells, including improving both the rate performance and longevity of cells. To address these challenges, the Faraday Institution, the UK's independent institute for electrochemical energy storage science and technology, launched the Lithium Sulfur Technology Accelerator (LiSTAR) programme in October 2019. This Roadmap, authored by researchers and partners of the LiSTAR programme, is intended to highlight the outstanding issues that must be addressed and provide an insight into the pathways towards solving them adopted by the LiSTAR consortium. In compiling this Roadmap we hope to aid the development of the wider Li–S research community, providing a guide for academia, industry, government and funding agencies in this important and rapidly developing research space.